Teaching English to Young Learners: : Why Translanguaging? - Idaryani; Reza Pahlevi Ginting; Sofia Hasmin Siagian; Netia Lestari (LPPM Universitas Malikussaleh, 2024)
The study aims to explore translanguaging strategies used by English language teachers in teaching English EFL to young learners at primary school level in Indonesia. The participants were two English language teachers and 60 students from the fifth and sixth grade at one of public primary schools, located in Lhokseumawe City, Aceh, Indonesian. The research employed a qualitative case study design. The data was collected based on observation and interviews. The results of the study showed that translanguaging improved leaners’ comprehension in terms of vocabulary retention for young learners in learning English as a foreign language. The results of the study are further discussed. Keywords: